Fake News and Journalistic "Rules of the Game". Issue 4 (2nd October 2019) - Wahutu, j. Siguru
ABSTRACT: The increase in social media use within African media fields has seen a concomitant increase in fears and concerns about "fake news" over the last few years. However, there is little empirical evidence that "fake news" has been as much of a menace as observers would have us believe. Much of the "fake news" excitement is anchored on panic by American news organisations following the 2016 US presidential elections. Nevertheless, recent scholarship shows that the effects of "fake news" on the US elections were largely exaggerated while the role of conventional media actors largely suppressed. This article argues that the circulation of "fake news" is intricately tied to traditional (western) media practices which have themselves been problematic. It contends that "fake news" is not the problem in and of itself, but rather a sign that African media fields need to reimagine how journalism is practised within the continent. As such, it maintains that studying African journalists not just as "carrier groups" (in the Weberian sense) but also as the primary definers of what the boundaries of the "Overton window" should be is more informative on "fake news" effects than the current fixation with social media's role in disseminating "fake news".